A surface-based cross-sectional fMRI study on brain function differences between comorbid mild or moderate depression and insomnia - Zhongxian Li; Zhongxian Li; Limei Chen; Limei Chen; Yingxin Huang; Yingxin Huang; Luda Yan; Luda Yan; Junquan Liang; Junquan Liang; Min Peng; Min Peng; et al. (Frontiers in Neuroscience)
BackgroundThe mechanisms of Comorbid mild or moderate depression and insomnia (CmiDaI or CmoDaI) are complex, and stratification remains poorly understood.MethodsResting-state fMRI data were collected from 32 patients with CmiDaI, 32 with CmoDaI, and 30 healthy controls (HCs). Data were analyzed using a surface-based computational method to examine differences in amplitude of low-frequency fluctuations (ALFF) and functional connectivity (FC) across the brain.ResultsSignificant ALFF differences were found in the left dorsolateral prefrontal cortex (DLPFC) between CmiDaI and CmoDaI. Compared to CmoDaI, CmiDaI showed increased ALFF in the left DLPFC, decreased FC between left DLPFC and right superior temporal gyrus, and increased FC in the right supramarginal gyrus (SMG) and right inferior frontal gyrus (IFG). Correlation analysis suggests lower left DLPFC ALFF correlated with more severe depression and insomnia. Lower FC between left DLPFC and right IFG was associated with more severe depression, while lower FC between left DLPFC and right SMG correlated with more severe insomnia.ConclusionOur findings suggest that reduced ALFF in the left DLPFC may serve as the potential biomarker to distinguish CmiDaI from CmoDaI, and offer insights for the two disorders’ treatments.